PERAN MEDIASI FINANCIAL BEHAVIOUR PADA FINANCIAL LITERACY TERHADAP FIRM PERFORMANCE - Augustin, Jeneva; Worokinasih, Saparila; Darmawan, Ari (FIA UB, 2020)
Financial literacy is a very important thing to be discussed further. In running a company or businesses in small, medium and large sectors, knowledge is needed to be able to run the business or company operations. This paper summarizes empirical research articles published between 2009 and 2019 that raise the topic of financial literacy. The articles reviewed in this paper look at the research gap, strengthen support for existing theories, and identify patterns among previous research. This review is expected to contribute theoretically to deepen the knowledge examined in financial literacy. Increased financial literacy in a person will be able to help companies to create reliable strategies. This reliable strategy can be seen with an increase in company performance. Firm performance in this case can be seen from a financial and non-financial perspective. Therefore, financial behavior is also a driving factor in improving the firm performance desired by business owners. financial behavior on a person will be motivated by financial literacy which can then improve firm performance. This paper aims to explain financial literacy, financial behavior and firm performance through previous studies or what is called literature review. Literature review in this paper will examine more closely related to financial literacy, financial behavior and firm performance.